Does the minimum wage have a higher impact on the informal than on the formal labor market? Evidence from quasi-experiments - Melanie Khamis (Institute for the Study of Labor (IZA), 2008)
This paper investigates a puzzle in the literature on labor markets in developing countries: labor legislations not only have an impact on the formal labor market but also an impact on the informal sector. It has even been argued that the impact on the informal sector in the case of the minimum wage is stronger than on the formal sector. Using quasi-experiments of minimum wage changes and thereby exploiting geographical variation of the minimum wage bite, I find evidence for this hypothesis. Informal workers, workers without social security contribution, experienced significant wage increases when the minimum wage was raised while formal workers did not. This result highlights that non-compliance with one labor legislation, the social security contribution, does not necessarily imply non-compliance to other labor laws such as the minimum wage.
urn:nbn:de:101:1-2009011973
Keywords: J31; J42; 330; Minimum wages; informal economy; quasi-experiments; Mindestlohn; Wirkungsanalyse; Informeller Sektor; Lohn; Entwicklungsländer